Comunicação e governança pública: estudo da comunicação nas cidades mais populosas do mundo - Nakazato, Cinthia Tiemi Iha (2019)
Information and Communication Technologies (ICTs) and the Internet are tools that can leverage levels of public governance by promoting transparency, civic participation and open dialogue between citizens and government. Thus, in order to continue the studies by Silva (2016), who studied public communication in Brazilian municipalities and concluded that there was no effective communication, it was also decided to investigate the international scenario of communication of the principles of public governance. We then analyzed the portals and social networks of the prefectures of the most populous capital cities in the world, being called “big cities”, according to the UN classification. In addition, to better understand the world scenario, the major cities selected were divided into continents: Africa, America, Asia, Europe and Oceania. The research can be classified as applied and descriptive and used as a design the study of multiple cases. For data collection, observation forms were used for portals and social networks and a questionnaire for city managers. The main perceived results, regarding the portals, were that the analyzed capitals intended to disseminate and dialogue with citizens about the principles of public governance, especially in America, Europe and Oceania. In social networks, the platforms were mostly sources of disclosure of the actions of city halls to the detriment of communication itself. From the questionnaire sent to the managers, nine capitals requested to be sent to other sectors or thanked the contact, but none returned with the answers. Thus, it was found that, similar to that found in the studies by Silva (2016), the international communication landscape of the principles of public governance is still shallow, since there was no effective communication on public governance between municipalities and citizens, both in social networks as in portals. This scenario can lead to the occurrence of any agency problems, distrust of citizens and informational asymmetry, but also provides opportunities for more effective public actions related to governance communication on the Internet.